2019
DOI: 10.26444/aaem/90979
|View full text |Cite
|
Sign up to set email alerts
|

A case of bovine tuberculosis in pigs in Poland – a country free from the disease

Abstract: Introduction. Bovine tuberculosis is a chronic contagious disease caused by Mycobacterium bovis or Mycobacterium caprae. Before widespread action conducted in Poland between 1959-1975 to combat bovine tuberculosis (BTB), about 40% of all tuberculosis cases in pigs was caused by the bovine bacillus. At the present time, correctly carried out, long-term control of cattle has resulted in cases of bovine tuberculosis in pigs and humans being extremely rare and sporadic. In pigs, tuberculosis is most often caught i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
(14 reference statements)
0
8
0
2
Order By: Relevance
“…Poland has maintained official TB-free status for over a decade although TB has been sporadically found in cattle and other species ( 6 , 19 , 23 ). The UK is one of the few countries in Europe that does not have TB-free status ( 5 ) and alpacas imported from that country jeopardise Poland’s TB status.…”
Section: Discussionmentioning
confidence: 99%
“…Poland has maintained official TB-free status for over a decade although TB has been sporadically found in cattle and other species ( 6 , 19 , 23 ). The UK is one of the few countries in Europe that does not have TB-free status ( 5 ) and alpacas imported from that country jeopardise Poland’s TB status.…”
Section: Discussionmentioning
confidence: 99%
“…From these, suspected mycobacterial isolates were detected in 60% of cases based on PCR genotyping methods. In Poland, authors Lipiec et al (2019) found M. bovis in two pigs maintained on the farm. Also in Poland, the correct and long-term control of cattle has resulted in sporadic cases of bovine tuberculosis in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in Germany a geographic division is shown: while in the northern part predominantly M. bovis is found, in the south, close to the alp region, M. caprae dominates [36]. Also in Poland both species are isolated from cattle with bTB [37]. Wild animals serving as bTB reservoirs are known in both countries.…”
Section: Discussionmentioning
confidence: 99%